Evolving digital leadership how to be a digital leader in tomorrow's disruptive world - Brett, James (Apress, 2019)
As a leader you need to constantly evolve to achieve sustained success. The world is being transformed by Digital. The pace of change is constantly accelerating and volatility and complexity are the new norms. Digital leaders are at the forefront of these waves of change, creating new markets and transforming traditional ones. This book is a framework and set of tools that will help you develop a deep awareness of yourself, your teams, and your stakeholders. The powerful four-step process (designed to remain relevant over time) ensures that you are embracing adversity, driving disruption, and unlocking your full leadership potential.
Includes bibliographical references. - Online resource; title from PDF title page (EBSCO, viewed July 6, 2018)
Keywords: Technological innovations -- Management; Innovations; Gestion; Research & development management; Economics; Organization & management of education; Organizational theory & behaviour; Business strategy; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Technological innovations; Management